Training for Posyandu Cadres to Support the Stunting Prevention Program: Pelatihan Kader Posyandu Guna Mendukung Program Pencegahan Stunting - Liza Fitri Lina; Ferasinta; Nopiawati (Universitas Lancang Kuning, 2025)
Stunting is a condition in which the body experiences a nutritional deficit over a prolonged period of time, resulting in a gangguan pertumbuhan, or a tinggi badan that is more severe than normal for humans. The main causes of stunting include inadequate nutrition and other health issues that arise during the first 1000 days of life. The more the government's stunting program is implemented, the more stunting occurs in the balita and the more prominent the dampak, the more urgent it is to conduct a konkrit. This aims to increase the knowledge and understanding of posyandu cadres about screening for stunting and the importance of stunting prevention. Education is provided to popsyandu cadres about the meaning of stunting, the causes and consequences of stunting, the impact of stunting, handling stunting, stunting screening, the role of cadres, targets, contraception progestin pills to support stunting. This service activity is carried out using lecture methods and stunting screening simulations. The lecture method to provide an explanation of stunting and simulation explains how stunting screening is carried out. The activity went smoothly and the participants understood and received the education and simulation very well, the cadres' understanding of the information provided reached 95% Good. proven by enthusiasm and answering questions correctly and practicing stunting screening correctly